Innovation, Strategic Planning, and Technology Adoption as Drivers of SMEs’ Performance - Ananda, Nova Adhitya; Amirul Mustofa; Eddy Yunus (International Journal of Economics, Business and Innovation Research, 2025)
Small and Medium Enterprises (SMEs) play a pivotal role in driving economic growth and employment, particularly in emerging economies. However, their performance is often constrained by limited resources, weak strategic alignment, and insufficient technological integration. Grounded in the Resource-Based View (RBV) and Dynamic Capabilities framework, this study examines the influence of innovation, strategic planning, and technology adoption on SMEs’ performance. Data were collected from 100 SME respondents in Indonesia using purposive sampling, and the analysis was conducted through Structural Equation Modeling (SEM) with SmartPLS 3.0. The findings demonstrate that strategic planning significantly enhances SMEs’ performance by improving internal alignment and market responsiveness. Innovation, while essential, shows inconsistent effects, as its benefits depend on managerial capability and resource readiness. Moreover, technology adoption emerges as a critical factor, strengthening the positive impact of strategic planning and mitigating the risks of poorly managed innovation. The results highlight that SMEs must balance innovation efforts with systematic planning while integrating technology to ensure sustainable competitiveness. This study contributes theoretically by advancing the integration of RBV and Dynamic Capabilities in SME performance research, and it provides practical insights for managers and policymakers to foster digital readiness, strategic orientation, and innovation driven growth.